2018
DOI: 10.1002/psp4.12358
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Models of Differential Bortezomib Signaling Across Several Cell Lines of Multiple Myeloma

Abstract: The heterogeneous polyclonal nature of multiple myeloma complicates the identification of protein biomarkers predictive of drug response. In this study, a pharmacodynamic systems modeling approach was used to link in vitro bortezomib exposure and myeloma cell death. The exposure‐response was integrated through a network of important protein biomarker dynamics activated by bortezomib in four myeloma cell lines. The pharmacodynamic models reasonably characterized the protein and myeloma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Although the k deg,GILZm was same in both sexes, it was interesting to find a pronounced intertissue variability in this parameter across liver and uterus, consistent with previous findings (Ayyar et al, 2017). Similar observations of a "systems variability" in the degradation rate constants for some signaling proteins across several lines of multiple myeloma cells was recently reported (Ramakrishnan and Mager, 2019). The AUEC of hepatic GILZ enhancement was significantly greater in females compared with males ( Fig.…”
Section: Systems Modeling Of Corticosteroid-estrogen Antagonismsupporting
confidence: 90%
“…Although the k deg,GILZm was same in both sexes, it was interesting to find a pronounced intertissue variability in this parameter across liver and uterus, consistent with previous findings (Ayyar et al, 2017). Similar observations of a "systems variability" in the degradation rate constants for some signaling proteins across several lines of multiple myeloma cells was recently reported (Ramakrishnan and Mager, 2019). The AUEC of hepatic GILZ enhancement was significantly greater in females compared with males ( Fig.…”
Section: Systems Modeling Of Corticosteroid-estrogen Antagonismsupporting
confidence: 90%
“…Our data support this particular combination of PIN/BTZ as being synergistic in reducing the viability of MM RPMI 8226 cells, although the extent of synergism seems to differ in the other two cell lines. Interestingly, BTZ has been shown to have similar effects in RPMI 8226 and U266 cells [ 42 ], while our study showed differing cytotoxic effects from PIN/BTZ in these two cell lines. Rather, we observed NCI-H929 cells to have similar cytotoxic effects to RPMI 8226 cells from PIN/BTZ treatment.…”
Section: Discussionmentioning
confidence: 43%
“…The mathematical model was validated qualitatively as a first effort, but importantly, the laboratory results confirm that the levels of caspase activation predicted biomarkers for clinical application (for example, see [48][49][50][51]). Here, two related rate constants that direct protein synthesis and degradation were found to contribute to the most variability in model output, caspase activation.…”
Section: Discussionmentioning
confidence: 79%
“…Sensitivity analyses have been commonly used following construction of computational ODE models to discover potential drug targets, therapy resistance, and other biomarkers for clinical application (for example, see [48][49][50][51]). Here, two related rate constants that direct protein synthesis and degradation were found to contribute to the most variability in model output, caspase activation.…”
Section: Discussionmentioning
confidence: 99%